(untitled) (Horizontes de Enfermería, 2019)
This research was carried out in the rural parishes of Chical, Maldonado and Tobar Donoso which belong to the Tulcán canton, Carchi Province. Its objective was to identify the risk factors of the metabolic syndrome in the young adult population (20 to 39 years) related to lifestyles. The metabolic syndrome, some years earlier, was more common in people from the age of 50. However, a growing prevalence has recently been demonstrated in young adults, it is because at this stage the individual must begin to assume social and family roles, which influences his/her way of life. A mixed approach with quantitative and qualitative descriptive cross-sectional data was used, it allowed describing each variable and subsequently correlating the risk factors that generate metabolic syndrome in a representative sample with a 5% margin of error and a level 95% confidence. We worked with 63 people with the ages under review and who do not have a diagnosis of chronic non-communicable diseases. This research used a survey, as a research technique, to identify lifestyles, control of anthropometric measures (weight, height and abdominal perimeter), control of blood pressure and complementary blood tests such as cholesterol, triglycerides and glucose. The research found 45% of abdominal circumference increase, 48% triglycerides in blood greater than or equal to 150 mg / dL, 47.6% low levels of HDL cholesterol and 8% elevation in blood pressure. It was concluded that the young adult population presents associated risk factors to generate metabolic syndrome directly related to lifestyles, which will increase the incidence of cardiometabolic diseases in this age group.